FERMION THEORETICAL-GROUP STUDY OF COLLECTIVE STATES OF NUCLEI - Baktybaev, K.B.; Koilyk, N.O.; Ramankulov, K.E. (Recent Contributions to Physics, 2008)
On the contemporary stage of development of the theory of nuclear physics construction and development theoretical-group approaches, based on exposure and generalization common fermion symmetrical properties, witch proceed from nuclear bounding force and from common foundation of description of the most important nuclear properties, is important problem.